Competência emocional como recurso para o envolvimento de adolescentes na escola - Sampaio, Joana (2021)
Emotional competence, an indicator of positive development in adolescence, is an explicative factor of academic success. However, research addressing relations among emotional competence and procedural variables of academic success, such as engagement in school, is still needed. This study examines whether emotional competence constitutes a personal resource for adolescents’ engagement in school, having controlled the effects for gender and school level. The Emotional Skills and Competence Questionnaire and the Four-Dimensional Scale of Students’ Engagement in School were completed by 303 adolescents of both genders (Mage = 16.36) attending high school. Results from a hierarchical multiple linear regression model suggested that emotional competence explains 34% of the variance of engagement in school. Implications for research and psychological intervention are discussed.